2008
DOI: 10.1021/la801487f
|View full text |Cite
|
Sign up to set email alerts
|

Film Thickness Dependence of Protein Adsorption from Blood Serum and Plasma onto Poly(sulfobetaine)-Grafted Surfaces

Abstract: In this work, we investigate protein adsorption from single protein solutions and complex media such as 100% blood serum and plasma onto poly(sulfobetaine methacrylate) (polySBMA)-grafted surfaces via atom transfer radical polymerization (ATRP) at varying film thicknesses. It is interesting to observe that protein adsorption exhibits a minimum at a medium film thickness. Results show that the surface with 62 nm polySBMA brushes presents the best nonfouling character in 100% blood serum and plasma although all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
216
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(232 citation statements)
references
References 39 publications
14
216
0
2
Order By: Relevance
“…The adhesion of organisms to surfaces in nature is even more complex as the surfaces are immediately conditioned by biomacromolecules, altering the surface properties for further attachment. 44,63 To summarize, we found that surface hydration and surface energy was higher for the 64 , pSBMA 30 , pHEMA and pHPMA 65 , as well as poly(HEMA-co-PEG10MA) (this study), suggest that this is a phenomenon with some generality, and our results demonstrate that this is not limited to protein fouling, but applies also to fouling of marine organisms. We note that the polymers listed above all have chains with functional side-groups.…”
Section: Biofouling Assayssupporting
confidence: 67%
See 1 more Smart Citation
“…The adhesion of organisms to surfaces in nature is even more complex as the surfaces are immediately conditioned by biomacromolecules, altering the surface properties for further attachment. 44,63 To summarize, we found that surface hydration and surface energy was higher for the 64 , pSBMA 30 , pHEMA and pHPMA 65 , as well as poly(HEMA-co-PEG10MA) (this study), suggest that this is a phenomenon with some generality, and our results demonstrate that this is not limited to protein fouling, but applies also to fouling of marine organisms. We note that the polymers listed above all have chains with functional side-groups.…”
Section: Biofouling Assayssupporting
confidence: 67%
“…With regard to how the antifouling properties depend of coating thickness, this has been studied for protein adsorption in a number of systems, including early and fundamental work on poly(ethylene glycol) (PEG) coatings, [27][28] and more recent work on both hydrophilic and zwitterionic polymers. [29][30] With regard to marine fouling, in particular, there appears to be few studies on how polymer layer thicknesses influence fouling behavior, apart from the well-documented studies on the influence of polymer (PDMS) thickness at the scale of tens to hundreds of micrometres on the adhesion strength of macrofouling. 22,31 In this work a series of random poly(HEMA-co-PEG10MA) copolymer films with thicknesses from 50 to 1000 Å have been prepared via surface-initiated atom transfer radical polymerization (SI-ATRP), and the influence of polymer thickness on antifouling performance against some marine fouling species was studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[32,43,58,59] The ''graft-to'' method involves (i) the preparation of polymers containing nonfouling and adhesive groups, such as 3,4-dihydroxyphenylalanine (DOPA) groups [24,60] and polylysine segments, [61] and (ii) the direct attachment of the polymers onto the surface. pSB and pCB have been grafted to or from surfaces via several common adhesive linkers, including thiols for a gold surface, [43,45,47,50,51,62,63] silanes for a glass surface, [64] hydrophobic moieties for a hydrophobic surface, [41,65,66] or DOPA for various surfaces, [67,68] or via interpenetrating networks (IPNs) into polyurethane (SPU) matrices. [69] pSB-based hydrogels have also been prepared.…”
Section: Ultralow Fouling Psb and Pcb Zwitterionic Materialsmentioning
confidence: 99%
“…While protein adsorption from single-protein solutions is not very sensitive to film thickness, protein adsorption from complex media such as undiluted blood plasma and serum depends on the film thickness. Protein adsorption on pSB-grafted surfaces of different film thicknesses [62] was first performed with two common proteins, i.e., fibrinogen (340 kD, pI ¼ 5.5, where pI ¼ isoelectric point) and lysozyme (14 kD, pI ¼ 12). From Figure 3a, it can be seen that all surfaces exhibit lysozyme and fibrinogen adsorption of <3 ng cm…”
Section: à2mentioning
confidence: 99%
“…pCBMA-1 C2 and control coatings were grafted by surface-initiated atom transfer radical polymerization (ATRP) onto a gold surface covered with initiators. The thicknesses of the obtained polymer coatings, as measured by atomic force microscopy (AFM), [26] were 26-32 nm (Table 1).The bactericidal activity of pCBMA-1 C2 surfaces was determined using E. coli K12, according to a modified literature procedure.[2] The permanently cationic poly(methacryloyloxyethyldimethyloctylammonium bromide) (pC8NMA, cationic control) and the zwitterionic poly (2-carboxy-N,N-dimethyl-N-[2'-(methacryloyloxy)ethyl]ethanaminium) (pCBMA-2, zwitterionic control) were used as the positive and the negative control surfaces, respectively (Scheme 1). The antimicrobial efficiency was defined as the amount of live cells on the tested surfaces relative to those on the pCBMA-2 surface.…”
mentioning
confidence: 99%